Utilization of Coconut Shell Waste into Energy: Training for Small and Medium Enterprises" in Pasar Minggu Area, South Jakarta - Arinda Ristawati; Aqlyna Fattahanisa; Riskaviana Kurniawati; Havidh Pramadika; Onnie Ridaliani Prapansya; M Mirza Ananta Ihza Hiswara (International Journal Of Community Service, 2025)
Indonesia is a tropical country with a wealth of coconut trees widespread in almost all of its territory, from Sumatra to Papua. This coconut tree has great potential that has not been fully utilized until now. Although almost all parts of the coconut have been utilized, most coconut fibers and shells are still wasted. This program aims to encourage sustainable and productive waste utilization and support the creation of independent and productive local entrepreneurs. With a focus on empowering SMEs based on local resources, this program is also expected to be able to contribute to improving the local economy and expanding employment. So that partner SMEs can produce high-quality coconut shell charcoal briquettes that are ready to be marketed and Increase the knowledge and technical skills of the trainees in processing coconut shell waste. The method of implementing the PKM program is carried out systematically through several stages to overcome the main problems faced by small and medium enterprises (SMEs) in Pasar Minggu, South Jakarta in the field of production, management, and marketing of briquette products from coconut shell waste. The implementation of this PKM program proves that with the right training, the community can be invited to utilize organic waste in products with economic value. One of the key aspects of the success of this program is involving the community in every stage of the activity. Thus, the community not only becomes passive beneficiaries but also plays an active role in the development of solutions that are by field conditions. Improving business management knowledge and skills is also an important point. The training conducted not only focused on the technical aspects of making briquettes but also on how to manage small businesses effectively with business management, as well as product marketing.